2002
DOI: 10.1021/jm020843w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spermine Conjugation on the Cytotoxicity and Cellular Transport of Acridine

Abstract: Polyamines are believed to be potent vectors for the selective delivery of chemotherapeutic agents into cancer cells. In this paper, we report the effect of spermine conjugation on the cytotoxic and transport properties of acridine. Six derivatives, composed of a spermine chain attached at its N(1) position to an acridine via an aliphatic chain, were synthesized. The aliphatic linker, comprised of 3-5 methylene units, was connected to the position-9 of the heterocycle through either an amide (amidoacridines 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
169
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(183 citation statements)
references
References 67 publications
12
169
0
2
Order By: Relevance
“…This property has already been used to strengthen the activity of several DNA-damaging agents, including topoisomerase II poisons (20,48). In this context, one can expect to increase the stability of epipodophyllotoxin/DNA/topoisomerase II ternary complexes by a stronger interaction of DNA with the positively charged polyamine chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This property has already been used to strengthen the activity of several DNA-damaging agents, including topoisomerase II poisons (20,48). In this context, one can expect to increase the stability of epipodophyllotoxin/DNA/topoisomerase II ternary complexes by a stronger interaction of DNA with the positively charged polyamine chain.…”
Section: Discussionmentioning
confidence: 99%
“…The antiproliferative effects of F14512 and etoposide have been evaluated according to a procedure described previously (20). Briefly, murine leukemia L1210 cells were cultivated in 96-well plates in the presence of F14512 or etoposide at appropriate concentrations and 500 Amol/L putrescine, 100 Amol/L spermidine, 50 Amol/L spermine, or physiologic saline as control in a medium containing 2 mmol/L aminoguanidine.…”
Section: Antiproliferative Activity In the Presence Of Additional Exomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, tagging spermidine analogues to a chemotherapeutic agent may enhance their activity either by facilitating uptake (via polyamine uptake systems) or by competition with polyamines for 'critical binding sites' in the cells. Indeed, it was demonstrated that linkage of polyamines to cytotoxic compounds facilitates their entry into tumor cells possessing a polyamine uptake system and increases their selectivity to DNA (8). Thus, the ability of the bifunctional alkylating agent chlorambucil, to form interstrand crosslinks with double stranded DNA, increased 10 4 -fold after conjugation with spermidine (9).…”
Section: Introductionmentioning
confidence: 99%
“…The polyammonium cations have proved to favor the interaction with the negatively charged phosphates of the DNA backbone maintaining a high degree of translational freedom along the polyanion backbone, thus conferring a high DNA affinity without modifying the capability of the drug to locate appropriate sites of DNA (11). Conjugation of a cytotoxic drug to polyamines gave successful conjugates with chlorambucil (12)(13)(14), nitroimidazole (15,16), aziridines (17)(18)(19), acridine (20), and enediynes (21), with enhanced cytotoxicity and/or increased drug selectivity for tumor cells.…”
Section: Introductionmentioning
confidence: 99%